2022
DOI: 10.5312/wjo.v13.i11.969
|View full text |Cite
|
Sign up to set email alerts
|

Role of the posterior deep deltoid ligament in ankle fracture stability: A biomechanical cadaver study

Abstract: BACKGROUND The deltoid ligament is a key component of ankle fracture stability. Clinical tests to assess deltoid ligament injury have low specificity. In supination external-rotation (SER) type-IV ankle fractures, there is either a medial malleolus fracture or deltoid ligament injury. These injuries are often considered unstable, requiring surgical stabilisation. We look to identify the anatomical basis for this instability. This study investigates the anatomical basis for such instability by re-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 37 publications
(41 reference statements)
2
11
0
Order By: Relevance
“…Our MCID for talar tilt instability was 7.0 degrees, consistent with a previous report. 16 No MCID value for defining rotational instability exists. Radiographic measurements were obtained using Sectra IDS7, version 23.2 (Sectra AB, Linköping, Sweden).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our MCID for talar tilt instability was 7.0 degrees, consistent with a previous report. 16 No MCID value for defining rotational instability exists. Radiographic measurements were obtained using Sectra IDS7, version 23.2 (Sectra AB, Linköping, Sweden).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that these are termed SER4a fractures 7 ; acceptable clinical and functional outcomes in the short and midterm have been reported after nonoperative treatment. 3,[6][7][8]13,15,16 However, the primary concern with nonoperative treatment of SER4a fractures is the risk of occult instability leading to PTOA in the long term. 7,14 This study builds on Gougoulias and Sakellariou's theory advocating that the superficial layer and deep anterior deltoid ligaments are injured whereas the deep posterior deltoid ligament remains intact in SER4a fractures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instability is indicated in 35% to 48% of ankle fractures when gravity stress tests are used 2-5 , but in only 1% to 3% of fractures when weight-bearing radiographs are used 2-4 , meaning that the ankle mortise often changes from nonanatomic to anatomic (i.e., an apparently unstable fracture to an apparently stable one) after the orientation of the leg is shifted and weight is applied to it. This is rationalized by a possible partial rupture of the deltoid ligament, with the deep posterior portion of the ligament remaining intact 3,6,7 . Some authors have suggested classifying such an injury as SER4a 3,6 .…”
mentioning
confidence: 99%
“…one) after the orientation of the leg is shifted and weight is applied to it. This is rationalized by a possible partial rupture of the deltoid ligament, with the deep posterior portion of the ligament remaining intact 3,6,7 . Some authors have suggested classifying such an injury as SER4a 3,6 .…”
mentioning
confidence: 99%